Softening the steps to gigantism in sauropod dinosaurs through the evolution of a pedal pad - Jannel, Andréas; Salisbury, Steven W.; Panagiotopoulou, Olga (Dryad, 2022)
How sauropod dinosaurs were able to withstand the forces associated with
their immense size represents one of the most challenging biomechanical
scenarios in the evolution of terrestrial tetrapods, but also one lacking
robust biomechanical testing. Here, we use finite element analyses to
quantify the biomechanical effects of foot skeletal postures with and
without the presence of a soft tissue pad in sauropodomorphs. We find that
none of the models can maintain bone stresses that fall within optimal
bone safety factors in the absence of a soft tissue pad. Our findings
suggest that a soft tissue pad in sauropods would have reduced bone
stresses by combining the mechanical advantages of a functionally
plantigrade foot and the plesiomorphic digitigrade saurischians
conditions. The acquisition of a developed soft tissue pad by the
Late-Triassic–Early-Jurassic may represent one of the key adaptations for
the evolution of gigantism that has become emblematic of these dinosaurs.
The raw dataset was collected in international museum collection. 3D
models were reconstructed via photogrammetry using Agisoft Photoscan
Professional v1.0.3 . 3D models were edited into Autodesk Maya 2017
(www.autodesk.com). Each 3D surface model was then cleaned and converted
into a volumetric mesh file of continuum linear tetrahedral elements of
types C3D4 using 3-Matic 11.0 software (Materialize Inc., Leuven,
Belgium). Finally, each mesh file was then imported into Abaqus/CAE
6.13-6.23 FEA software where the full set of analysis was performed.
All *.inp files may initially be opened with any text editors and into
Abaqus/CAE FEA software for further analysis to be undertaken. Note: a
valid license of Abaqus would be required to open the *.odb files as the
number of node of all of our model exceed the free viewer of 1000 nodes.
The *.inp files include the full set of postural morphotype for each
specimen. The FEA results for each of our analysis presented in our main
text. A detailed explanation of the file extension is provided in the
README.txt file.
Keywords: FOS: Biological sciences; Dinosauria; Functional morphology; Finite element analysis; pad; pes; Stress distribution; Gigantism